O Jovem Infrator na Visão dos Profissionais da Febem – Rio Claro - Rosalen, Patricia Cristina (2008)
The present article intends how the professionals that act togegher of offender youngs, perceive that the motives (causes) that take them to that situation, opposing those perceptions to the bibliographical studies. For so much, were realized interviews with a Psychologist ans a Social Worket that act in the office of FEBEM in the municipality (district) of Rio Claro.